THE CONTRIBUTION OF SUBTITLED AUDIO-VISUAL SUPPORT TO ORAL COMPREHENSION AND TO VOCABULARY IN A UNIVERSITY ENVIRONMENT - Abdelli KANDSI; Fatima KEBAILI (Universitaria Publishing House, Craiova, 2024)
This article is part of a didactic perspective. He is interested in oral didactics in a university setting. Through this experimental research, we wanted to demonstrate that the interaction between subtitles and visual modality is an essential contribution to oral comprehension (global and detailed) and vocabulary learning through the subtitled audio-visual medium. Our method consists of using a video in two modes of presentation with two distinct groups: the first without subtitles and the second with subtitles. We also used an experimental post questionnaire to find out if students would have liked to have had the text transcribed.